Respuesta :

Answ

0

=

x

2

2

x

35

=

x

2

2

x

+

1

1

35

=

(

x

1

)

2

36

=

(

x

1

)

2

6

2

=

(

(

x

1

)

6

)

(

(

x

1

)

+

6

)

=

(

x

7

)

(

x

+

5

)

So

x

=

7

or

x

=

5

I used the difference of squares inequality along the way:

(

a

2

b

2

)

=

(

a

b

)

(

a

+

b

)

Step-by-step explanation:

Mibo

Step-by-step explanation:

x2 + 2x - 35 = 0

x2 + 7x - 5x - 35

x(x + 7) - 5(x + 7)

(x - 5) (x + 7) = 0

x - 5 = 0. x + 7 = 0

x = 5. x = - 7